PENGARUH MEANS ENDS ANALYSIS BERBASIS MEDIA KARTU KENDALI LITERASI DIGITAL TERHADAP KEMAMPUAN NUMERASI REPRESENTASI MATEMATIS SISWA SEKOLAH DASAR - Acep Saepul Rahmat (Jurnal Penelitian Kebijakan Pendidikan, 2021)
Students' difficulties in understanding mathematics subject matter during the COVID-19 pandemic were one of the challenges that arose in distance learning. Students did not understand the material substantively and holistically because of the limited space and time to study. Students also continuously showed difficulty in solving mathematical numeracy problems. Success in solving mathematical numeracy problems depends on the representations used. Model Means Ends Analysis (MEA) is a strategy to analyze a problem through various ways to achieve the desired end goal. In this study, MEA was supported by the application of Digital Literacy Card (KKLD) media by using powerpoint and geogebra applications. The purpose of this study was to determine the effect of the application of MEA based on the Digital Literacy Card (KKLD) media on the numeracy skill of mathematical representations. The research method used was a quantitative, quasi-experimental research design with the nonequivalent pre-test-post-test control group design. The population in this study were students of class V-A at SDN Kampung Bali 07 Pagi, amounting to 24 students as the experimental class and 24 students in class V-B SD Negeri Bendungan Hilir 05 as the control class. The instrument used was the rubric of mathematical representation numeracy skills. The average test results showed the post-test value of the experimental class is 80, and the control class is 64.17. The results of the test of the average difference of one sample in the experimental class showed an increase in the numerical ability of students' mathematical representation with the MEA model based on the Digital Literacy Card (KKLD) media and the test results of the difference in the mean of two samples on the post-test value showed that the mathematical representation ability of students who received the MEA model was better compared to students who received conventional learning. This proves that the MEA based on the Digital Literacy Card (KKLD) media has an effect on the numeracy skill of the mathematical representation of the fifth grade elementary school students.